Public transport route network optimization criteria’s for cities - Ušpalytė-Vitkūnienė, Rasa; Kolodinskaja, Justina (International Conference “Environmental Engineering”, 2020)
The city’s approach to transport management is defined by the City Master Plan and City Strategic Plan and Vilnius Sustainable Urban Mobility Plan (Vilnius Sustainable Mobility Plan − SUMP, 2018), which have identified scenarios for the transportation system till 2030. A SUMP fosters a balanced development of all relevant transport modes, while encouraging a shift towards more sustainable modes. Its key objective is to design a modern, efficient, fast, comfortable and safe public transport system, comparable to those of EU capital cities. Vilnius aims to maintain an environmentally friendly public transport fleet that represents the biggest share in the city’s modal split. Still there is a problem with matching the public transport network with the fast changing urban situation. Citizen’s are moving from one part of the city to the other, that shows that is necessary to have tool helping to decide how and when to change public transport route. The aim of this research was to create the clear methodology for the public transport route network maintenance based on the main public transport route criteria’s.
Keywords: public transport; route network; criterion analysis